The inhibitory effects of Andrographolide, Evodiamine and Cisplatin in Cervical Cancer Cells - Lavanya, S.K.; N. Palanivel; Sundaresan, S. (The Indian Veterinary Journal, 2023)
Cervical cancer could be inhibited by supplementing with bioactive molecules that decrease the proliferation and differentiation of cervical cancer cells and promote cell death. Andrographolide is diterpenoid that have strong anticancer properties. EVO has a number of biological activities, including anticancer, and antinociceptive qualities. Cisplatin is extensively used in the treatment of several human ailments and have great therapeutic results. This drug is also used as a pharmaceutical to counteract tumors. Based on these properties, we investigated the anti-proliferative efficiency of andrographolide (andro), evodiamine (evo), and cisplatin (cis) against cervical cancer cells in vitro. This was measured by cytotoxicity assay in human cervical cancer cells, which showed increased activity in andrographolide and evodiamine compared with cisplatin in a dose- and time-dependent manner. As a result, it is concluded that andrographolide, evodiamine, and cisplatin may repress the proliferation of HeLa cells by increasing cell inhibition and reducing cell viability and their activities.